Phonetics Symbol As Tool For Correct Pronouncing English - Budiman Budiman; Khairul Azmi; Yani Lubis (Universitas Maritim AMNI Semarang, 2023)
This study aims to inform that an understanding of phonetic symbols is needed to assist in pronouncing. This study uses library research, this study uses student observation by giving students a few words or sentences and then students read it. The result, students of the Department of English at Negeri Padang University in 2015 were said to have good skills in pronouncing the vowels of English words. The average is 66.1. There are 9 excellent students here.